Pengaruh Budaya Organisasi, Kerja Tim, dan Profesionalisme terhadap Organizational Citizenship Behavior Guru Madrasah Aliyah Negeri Surakarta Jawa Tengah - Slamet Budiyono; Ngatmin Abbas (CV. Creative Tugu Pena, 2024)
The objective of this research was to studies the effect of organization culture, team work, and professionalism to organization behavior citizenship of teacher’s Madrasah Aliyah Negeri in Surakarta Central Java. The research was conducted by using survey method with path analysis applied on testing hypothesis. The target population size of this research is 579 of teachers. Research samples selected as much as 237 teachers using simple random sampling technique. Based on this research of data obtained the following conclusions: (1) the organization culture has positive direct effect to organization behavior citizenship of teacher’s, (2) the team work as positive direct effect to organization behavior citizenship of teacher’s, (3) professionalism has positive direct effect to organization behavior citizenship of teacher’s, (4) the organization culture has positive direct effect to professionalism,(5) team work have positive direct effect to professionalism. The conclusion is that the teacher’s organization behavior citizenship is effected by the organization culture, team work, and teacher’s professionalism